Q Fever Endocarditis: A Challenging Diagnosis in a Patient Referring Weight Loss and Anorexia, and With Granulomas in Gastric Biopsy Specimens - Ana Elena Lago‐Rodriguez; Pablo Arturo Fraile‐Ribot; Isabel Amengual‐Antich; Francisco Gual‐Capllonch; Mercedes Garcia‐Gasalla (Clinical Case Reports)
ABSTRACT Diagnosis of Q fever endocarditis is challenging since clinical findings are non‐specific and diagnosis is mainly made by indirect methods such as serology. A progressive constitutional syndrome, severe asthenia, anorexia with no fever and histopathological findings of non‐necrotizing gastric granulomas in a gastric biopsy were found preceding a cardiac failure in our case report. Prolonged treatment with doxycycline and hydroxychloroquine is mandatory, and cardiac valve surgery may be needed.